Studi Komparatif Pandangan Mahasiswa Mengenai Model Pemilihan Kepala Daerah Analisis Terhadap Asas Demokrasi dan Kedaulatan Rakyat - Ahmad Najmi Faris; Marlina; Ariansyah Mustafa; Dekick Jacinda One Alvina; Debbie Ananto Wahyu Pratama; Izza Safira (Journal Social Politica, 2026)
This article aims to conduct a comparative study of students' perspectives on regional head election models (Pilkada), focusing on their compatibility with the principles of democracy and people's sovereignty. The method is a sociological approach to law, used to investigate students' perceptions and political behavior regarding the regional head election system. The analysis used a comparative-descriptive approach, comparing applicable principles and theories with sociological realities through the distribution of questionnaires to students in the Malang Raya region. Based on student responses, 86.9% of respondents believed the representative system (DPRD) could not fully represent the people's mandate. Direct elections were considered to better guarantee political equality (one man, one vote), which could ensure the implementation of democratic principles and become an effective form of social control, compared to the representative system, which was feared to trigger transactional politics. Although the majority of students preferred direct regional elections, they mentioned several weaknesses of direct elections, such as high political costs due to money politics and the risk of social polarization, which could potentially undermine people's sovereignty. This indicates that students are more in favor of direct regional elections despite several unresolved weaknesses and their concern for the regional election system in Indonesia, while still prioritizing the principles of democracy and people's sovereignty.